THE DEVELOPMENT OF CLUSTERS AS A WAY TO INCREASE COMPETITIVENESS OF BUSINESSES (CASE OF MILK PROCESSING INDUSTRY IN TIRANA) - Patushi, Sadete; Kume, Vasilika (European Scientific Journal, ESJ, 2014)
The aim of the study is the suggestion of cluster development as a way to increase competitiveness in business and as the main way for the effective use of the potential of the dairy processing industry through policy guidance and their management to meet the challenges of today and future. The study provides an overview of the dairy sector, focusing primarily on its properties in the region of Tirana. The study consists in identifying possible strategies and solutions to enhance the competitiveness of the sector, which despite its steady growth faces a number of challenges and barriers. The implementation of quality standards and food safety, lowering the cost of raw materials and increased quality are elements on which depends directly competitiveness of the sector. The sector suffers from a lack of cooperation between all stakeholders in the supply chain. In this framework paper aims to analyze the clusters as a way to increase competition and cooperation at all levels of the value chain in the dairy processing industry. In this context, the study points to a growing need for enhanced cooperation horizontal, vertical and lateral in order to increase competitiveness by increasing productivity, lowering costs and better control the quality from raw materials to the final product, in terms of efficient management of the food supply chain. At the same time, the study shows the need for more effective policy making by policymakers to increase the competitiveness of the sector.